Syzygium paniculatum Brush Cherry - Edward Gilman (EDIS)
This document provides an overview of Syzygium paniculatum, commonly known as Brush Cherry. It describes the plant’s attractive reddish foliage that matures to dark green, and its small, shiny leaves. The document highlights the plant’s growth habits, including its potential to reach up to 12 feet in height, and its common use as a hedge in residential landscapes. It also covers the plant’s white flowers, which are often pruned off but can be quite showy when left to bloom. Additionally, the document discusses the plant’s adaptability to various soil types, its high drought tolerance, and its minimal pest issues, making it a versatile choice for different landscaping needs. Original publication date October 1999.